MENINGKATKAN KEMAMPUAN KEAKSARAAN MELALUI PERMAINAN ULAR TANGGA PADA ANAK USIA DINI KELOMPOK B1 DI TK YUNICO KOTA JAMBI - Piona; Destrinelli; Masyunita Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The issue of low literacy skills among early childhood learners remains a critical concern in preschool education, particularly in recognizing letters, reading, and basic writing. Preliminary observations at TK Yunico, Jambi City, revealed that most children in group B1 had not yet achieved the expected literacy development indicators. This study aims to improve early childhood literacy skills through the use of a modified educational snakes and ladders game. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles comprising planning, action, observation, and reflection. The subjects were 18 children aged 5–6 years from group B1, selected through a saturated sampling technique. Data were collected using observation, interviews, and documentation, with the main instrument being an observation sheet aligned with the literacy indicators in the Indonesian Ministry of Education Regulation No. 137 of 2014. The findings showed a significant improvement from the pre-action stage (30.6%) to the end of Cycle I (67.9%), and further to 86.7% by the end of Cycle II. These results demonstrate that the snakes and ladders game can serve as an enjoyable and effective alternative learning medium to enhance early literacy. The game successfully stimulated children's active participation, motivation, and engagement in foundational literacy activities.